Pengaruh Pengetahuan Gizi Ibu dan Kepatuhan Konsumsi Tablet Fe Terhadap Kejadian Anemia pada Ibu Ibu Hamil - Ermawati Ermawati; La Ode Muhamad Sety (NHM PRESS, 2023)
Anemia is a condition of below normal levels of hemoglobin in the blood and one of the nutritional problems in public health in developing countries. The prevalence of anemia in pregnant women in Southeast Sulawesi in 2018 was 10.5% where the highest prevalence was in Muna Regency at 40.69%, North Buton Regency, 36.2% of pregnant women in North Buton experienced anemia. This study aims to determine the factors that influence the incidence of anemia in pregnant women in North Buton Regency. This research is an analytic observational study with a cross sectional approach. The study involved 240 pregnant women as samples taken by random sampling technique. Data collection techniques using questionnaires / questionnaires. The data that has been collected is then analyzed statistically with the chi square test at a 95% confidence level (α = 0.05) to determine the effect between the independent variable and the dependent variable. The results of the analysis of the influence between the independent variables and the dependent variable obtained the nutrition knowledge factor of pregnant women with a value of p = 0.000; consumption level of nutrients with a value of p = 0.000 and adherence to consumption of Fe tablets with p = 0.000). Thus it can be concluded that the factors of knowledge about nutrition and adherence to consumption of Fe tablets have an effect on the incidence of anemia in pregnant women in North Buton Regency.